COMPONENTS OF FOLK PEDAGOGY AS A FACTOR OF PRESERVING NATIONAL IDENTITY - AND AN ETHNOCARRIER OF ETHNIC SOCIALIZATION (EDUCATION IN THE 21ST CENTURY, 2023)
The millennial experience of folk pedagogy has identified a number of effective means influencing the formation of personality, which are most concentrated in folk folklore: myths, legends, epics, fairy tales, folk miniatures (fable, proverb, saying, riddle, etc.), songs, family life,  traditions. The latter are components that have educational potential, which directly contribute to the formation of national consciousness of the ethnocarrier , historical and cultural system of values.      Nowadays, the study of national pedagogical culture has become more relevant and important. In folk pedagogy there are no strictly formed rules of education, systematized knowledge, specific scientific concepts. The creator of folk pedagogy is the people who, without books and special essays, have always sought and found effective means and found effective ways to prepare a new generation for life and work. Nowadays, the study of national pedagogical culture has become more relevant and important. In folk pedagogy there are no strictly formalized rules of education, systematic knowledge, specific scientific concepts. The formation of a modern ethnocarrier is an important motive of folk education in folk pedagogy. This problem is especially important nowadays, because there is a danger from powerful superpowers to turn the Armenian society with its long and peculiar historical past into a community of only historical value (folklore). From this point of view, in order to resist such approaches, to preserve their special place in the preservation of national identity, the components of folk pedagogy play their special place and role as a factor of ethnic socialization and the formation of the personality of the Armenian people.       Within the framework of this article, we have identified fairy tales, proverbs, sayings, riddles and folk songs from folk folklore that influence the formation and socialization of personality. The latter are of particular importance in folk pedagogy, exerting their influence on the education, upbringing and development of generations.
Keywords: Folk pedagogy; national identity; national consciousness; national profile; ethnic socialization; personality formation; components of folk pedagogy; ethnic education and upbringing; formation of national value system